ROLE OF BOARD OF COMMISSIONERS CHARACTERISTICS AND AUDIT COMMITTEE CHARACTERISTICS ON EARNING MANAGEMENT PRACTICES WITH AUDITORS’ REPUTATION AS MODERATORS DURING COVID-19 PANDEMIC - Dwi Nova Wijaya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The study aims to analyze the characteristics of the board of directors and audit committee of companies that are listed on the Indonesia stock exchange. It will also look into their earning management practices during the pandemic. The sample was obtained through a purposive sampling method. It was selected from the various observation periods of the Indonesia stock exchange's benchmark index, the Kompas-100. Data analysis was carried out using a combination of data panel and moderated regression techniques. The results of the study revealed that the size of the board of commissioners and the audit committee of companies significantly decreased the earning management practices of companies during the pandemic. On the other hand, the increase in the number of audit committee members also increased the earning management practices of companies. A reputable audit and an independent committee were instrumental in decreasing the activities of companies in their earnings management. This study is novel as it investigated the relationship between variables during the pandemic situation.JEL: G34.